MILAN SUNKO – A FORGOTTEN WORLD RENOWNED CROATIAN HERALDIC ARTIST (Review of Croatian History, 2022)
Milan Sunko (Zidani Most, 5 December 1860 – Zagreb, 9 March 1891) was a heraldic artist, numismatist, and collector, who studied and started his carrer in Vienna working with the most renowned heraldists of the “classical” Austrian heraldic period. He moved to Zagreb where he made number of well received paintings and graphics and was supported by the intelectual elite of the fastly developing city. His brief spectacular carrier was abruptly ended by laryngeal tuberculosis, and he died in his 31st year. His works are preserved in several museums and galleries in Zagreb, and his heraldic lithographs and ex libris bookplates are remembered in specialized bibliography. However, the Croatian heraldic historiography has forgotten all about him and this paper attempts to remedy this. After the establishment of the Brotherhood of Croatian Dragon Society – one of its founders being Emilij Laszowski, notable Croatian heraldist; it took upon a project to preserve Sunko’s grave, exhuming his remains and providing a modest but dignified grave for him at the Zagreb cemetary in 1910. To achieve that, the Draconian Society raised funds in an international action, activating his foreign friends and fans, documenting the project in respectable heraldic periodicals.